2023
DOI: 10.1155/2023/5540574
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-Resistant Environmental Bacteria Isolated Using a Network of Honey Bee Colonies (Apis mellifera L. 1758)

Giovanni Cilia,
Ilaria Resci,
Raffaele Scarpellini
et al.

Abstract: The phenomenon of antibiotic resistance stands as a paramount health challenge in the contemporary era. Within a One Health approach, it becomes crucial to effectively track the dissemination of antibiotic resistance, not only within humans and animals but also within the environment. To investigate the environment, the honey bee (Apis mellifera) has emerged as a prominent environmental bioindicator due to its social, behavioral, and morphological features. The objective of this study was to describe the antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Also, in a previous study featuring the resistome of two species of bees (Apis mellifera and Apis cerana) [48], Gilliamella apicola was found to be among the major contributors to the resistance against beta-lactams, among others. Accordingly, antimicrobial susceptibility tests performed in a previous study reported that over 50% of the bacterial isolates demonstrated resistance to penicillin, among other antibiotic classes, suggesting the potential role of bees as the bioindicator of the circulating environmental AMR [49]. Moreover, honeybee exposure to veterinary drugs highlights modest changes in the microbiota architecture as compared to the qualitative rearrangements featured by increased AMR genes as detected by qPCR [50].…”
Section: Metaproteomics Exploration Of the Bee Gut Microbiota Underli...mentioning
confidence: 93%
“…Also, in a previous study featuring the resistome of two species of bees (Apis mellifera and Apis cerana) [48], Gilliamella apicola was found to be among the major contributors to the resistance against beta-lactams, among others. Accordingly, antimicrobial susceptibility tests performed in a previous study reported that over 50% of the bacterial isolates demonstrated resistance to penicillin, among other antibiotic classes, suggesting the potential role of bees as the bioindicator of the circulating environmental AMR [49]. Moreover, honeybee exposure to veterinary drugs highlights modest changes in the microbiota architecture as compared to the qualitative rearrangements featured by increased AMR genes as detected by qPCR [50].…”
Section: Metaproteomics Exploration Of the Bee Gut Microbiota Underli...mentioning
confidence: 93%